2000
DOI: 10.1037/0022-3514.78.6.1024
|View full text |Cite
|
Sign up to set email alerts
|

Automatic vigilance: The attention-grabbing power of approach- and avoidance-related social information.

Abstract: The automatic processing of information was investigated, varying valence (positive vs. negative) and relevance (other-relevant traits [ORT] vs. possessor-relevant traits [PRTj; G. Peeters, 1983) of stimuli. ORTs denote unconditionally positive or negative consequences for persons in the social environment of the holder of the trait (e.g., honest, brutal) whereas PRTs denote unconditionally positive or negative consequences for the trait holder (e.g., happy, depressive). In 2 experiments using the Stroop para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
358
5
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(407 citation statements)
references
References 58 publications
(108 reference statements)
35
358
5
7
Order By: Relevance
“…First, consistent with previous literature (Bamford & Ward, 2008;Chen, M and Bargh, 1999;De Houwer et al, 2001;Duckworth et al, 2002;Neumann & Strack, 2000;Rotteveel & Phaf, 2004;Solarz, 1960;Wentura et al, 2000) we see a reaction time (RT) congruency effect: participants are faster to approach than avoid pleasant emotional stimuli, but faster to avoid than approach unpleasant stimuli. This reflects the automatic predisposition to approach pleasant and avoid unpleasant stimuli, and the additional effort required to regulate these tendencies when required.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…First, consistent with previous literature (Bamford & Ward, 2008;Chen, M and Bargh, 1999;De Houwer et al, 2001;Duckworth et al, 2002;Neumann & Strack, 2000;Rotteveel & Phaf, 2004;Solarz, 1960;Wentura et al, 2000) we see a reaction time (RT) congruency effect: participants are faster to approach than avoid pleasant emotional stimuli, but faster to avoid than approach unpleasant stimuli. This reflects the automatic predisposition to approach pleasant and avoid unpleasant stimuli, and the additional effort required to regulate these tendencies when required.…”
Section: Discussionsupporting
confidence: 78%
“…Participants have faster reaction times (RT) when performing congruent than performing incongruent actions. This confirms the automatic predisposition to approach pleasant and avoid unpleasant stimuli, and highlights the additional effort needed to regulate these tendencies when required (Bamford & Ward, 2008;Chen & Bargh, 1999;De Houwer, Crombez, Baeyens, & Hermans, 2001;Duckworth, Bargh, Garcia, & Chaiken, 2002;Krieglmeyer, De Houwer, & Deutsch, 2012;Neumann & Strack, 2000;Rotteveel & Phaf, 2004;Solarz, 1960;Wentura, Rothermund, & Bak, 2000). The difference in the speed of the response on congruent compared to the incongruent trials has been termed a congruency effect; for example a large congruency effect would be observed when comparing congruent trials with very fast responses to incongruent trials with very slow responses, whereas more similar response times for congruent and incongruent trials would represent a smaller congruency effect.…”
Section: Introductionmentioning
confidence: 53%
“…We are not aware of any precedent for this finding, but it may comport with other results showing that words suggesting a more palpable threat to the self, as should be the case for anger relative to fear stimuli (Wentura, Rothermund, & Bak, 2000), are recognized faster (Wurm & Vakoch, 2000). On the other hand, there was no main effect for Font Color, F (1, 95) = 1.51, p = .22.…”
Section: Results Involving Categorization Speedmentioning
confidence: 96%
“…These authors concluded that just as observed for familiar stimuli (Chen & Bargh, 1999), the evaluation of novel stimuli has immediate and direct consequences for approach and avoidance behavior tendencies. In a related study by Wentura, Rothermund, and Bak (2000), subjects participated in a go/no-go lexical decision task in which they had to withdraw their finger from a pressed key ("avoid") or had to press a key ("approach") if a word was presented. Responses to negative words were relatively faster in the withdraw condition, whereas responses to positive words were relatively faster in the press condition.…”
Section: Unpleasant Stimuli and Sustained Task Interferencementioning
confidence: 99%